BANKING LOAN PORTFOLIO OF UKRAINE: ANALYSIS, FACTORS, TRENDS - Kharchenko, Anatoliy (Socio-economic relations in the digital society, 2020)
Lending activity occupies a leading place in the structure of active operations of banks and ensures the formation of a significant part of the bank’s income. Therefore, it becomes necessary to study the quality of loan portfolio formation; determining the negative consequences of the impact of a low-quality loan portfolio for an individual bank and for the system as a whole; identification of factors that shape the risks of credit activities.The purpose of the article is to highlight the results of the analysis of the dynamics of formation, as well as the quality of the loan portfolio of Ukrainian banks in the period 2011—2019.In the course of the study, general scientific methods were used, in particular: methods of theoretical generalization — to study the theoretical foundations and some existing aspects regarding the factors influencing the riskiness of credit activity; system analysis — in the study of low-quality loan portfolio of the banking system; methods of graphic and statistical research — for analyzing and assessing the dynamics of overdue, non-performing loans in the portfolio and reserves that were formed for them.The proposed classification of credit risk factors orients the bank’s credit monitoring to a comprehensive analysis of the quality of the loan portfolio, taking into account the external and internal environment, which allows making timely decisions and preventing uncontrolled increase in problem loans. The obtained results of the research are focused on the quality of the loan portfolio, in particular, on the volumes of overdue and non-performing loans of banks and allow carrying out further scientific research of ways to solve the existing problem.The results of the study sharpen the focus on the quality of the loan portfolio, in particular, on the volume of overdue and non-performing bank loans. This will allow further research on ways to solve the existing problem.
Keywords: bank; loan portfolio; credit risks; non-performing loans; overdue debt; reserves